2020
DOI: 10.22630/mibe.2020.21.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Pricing European Options in Selected Stochastic Volatility Models

Abstract: In this paper four methods of calculating characteristic functions and their application to selected stochastic volatility models are considered. The methods applied are based on the assumption that the prices of European calls are evaluated numerically by means of the Gauss-Kronrod quadrature. Such approach is used to investigate computational efficiency of pricing European calls. Particular attention in this matter is paid to the speed of generating theoretical prices of the analyzed contracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The results of the research carried out are shown in the graphs below -see Figures 3 and 4. The results obtained allow to state that the conclusions drawn previously [Orzechowski 2020] can be extended onto the double Heston model. It means that the computational efficiency of pricing European options depends on the way the characteristic functions and their inverse Fourier transforms are calculated.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The results of the research carried out are shown in the graphs below -see Figures 3 and 4. The results obtained allow to state that the conclusions drawn previously [Orzechowski 2020] can be extended onto the double Heston model. It means that the computational efficiency of pricing European options depends on the way the characteristic functions and their inverse Fourier transforms are calculated.…”
Section: Resultssupporting
confidence: 62%
“…The determination of the most efficient approach both in the Heston and the double Heston models, is based on the results generated with the use of codes developed in Mathematica 10.2. The methodology proposed in the research is compatible with the approach applied previously [Orzechowski 2020]. It means that the theoretical prices of European calls have been evaluated numerically by means of the Gauss-Kronrod quadrature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation